Floristic Diversity and Conservation Value of Tanoe-Ehy Forest in South-Eastern (Cote d’Ivoire) - Koffi, Missa; Doudjo, Ouattara Noufou; Adama, Bakayoko (European Scientific Journal, ESJ, 2018)
The Tanoe-Ehy Forest, located in the South-Eastern of the Côte d’Ivoire is one of the rare forest cover of this type that still exists in the Country. These Forest was identified as a top priority site for conservation in West Africa. However, this important forest is subject to strong anthropogenic pressures which through poaching, uncontrolled takeoffs of natural resources and some agricultural clearing. A Botanical study based on plots, itinerant and linear inventory conducted in this forest intends to assess the plant species diversity and the conservation value for biodiversity of this forest. At the end of the study, 432 plant species were recorded. Among them, 14 are listed on endemic of Upper Guinea and 16 threatened and endangered list of species. Concerning the species threatened and endangering, 3 species are really in endangering (Hemandradenia chevalieri, Tieghemella heckelii, Irvingia gabonensis) and 13 others are a category of vulnerable species. A Sassandrian species of type II (Piptostigma fugax) was also observed. The dominant species of the forest are Symphonia globulifera and Uapaca paludosa. Concerning the vegetation condition, the swamp forest, the dry land forest and the raphiale vegetation have a high conservation value.